2018
DOI: 10.1111/neup.12505
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Creutzfeldt–Jakob disease with glial PrPRes nuclear and perinuclear immunoreactivity

Abstract: Proteinase K-resistant prion protein (PrP ) nuclear and perinuclear immunoreactivity in oligodendrocytes of the frontal cortex is found in one case of otherwise typical sporadic Creutzfeldt-Jakob disease (sCJD) type VV2a. The PrP nature of the inclusions is validated with several anti-PrP antibodies directed to amino acids 130-160 (12F10), 109-112 (3F4), 97-102 (8G8) and the octarepeat region (amino acids 59-89: SAF32). Cellular identification and subcellular localization were evaluated with double- and triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…These findings corroborate the relative resistance of the oligodendrocyte cell line in comparison with the reaction of astrocytes and microglia to PrP SC in a validated model of human CJD. Nevertheless, our results also confirm that oligodendrocytes are vulnerable at advanced stages of murine CJD, as they have previously been noted to be in human sCJD [11][12][13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings corroborate the relative resistance of the oligodendrocyte cell line in comparison with the reaction of astrocytes and microglia to PrP SC in a validated model of human CJD. Nevertheless, our results also confirm that oligodendrocytes are vulnerable at advanced stages of murine CJD, as they have previously been noted to be in human sCJD [11][12][13].…”
Section: Discussionsupporting
confidence: 91%
“…Oligodendrocyte abnormalities may contribute to explain ultrastructural white matter myelin alterations in CJD, and other natural and experimentally induced animal prionopathies [11,[21][22][23]. Moreover, oligodendrocyte alterations described in CJD [11][12][13] and present experimental model may link transition between mild to moderate white matter involvement in common forms compared with severe white matter involvement in panencephalopathic forms of CJD [24][25][26][27][28]. Although alterations of the white matter parallel the intensity of lesions of the grey matter in cases with long duration of the disease [28,29], pioneering panencephalopathic cases, described principally in Japan, were in favour of a primary alteration of the white matter [24,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of information on this matter invites further inquiry. Rarely, PrPRes can be seen in the nucleus and perinuclear region in oligodendrocytes in CJD (Fernandez-Vega et al, 2018) (Fig. 9).…”
Section: Creutzfeldt-jakob's Disease (Cjd) and Other Prion Diseasesmentioning
confidence: 84%
“…In contrast, oligodendrocytic PrP pathology has rarely been described. Fernandez-Vega et al [5] reported the presence of nuclear and perinuclear PrP d in oligodendrocytes in the frontal white matter in a 66-year-old man with an otherwise classical VV2-histotype, who had a disease duration of 4,5 months. We also observed the presence of oligodendroglial PrP d pathology in the white matter of some sporadic CJD cases.…”
Section: Introductionmentioning
confidence: 99%